Ambient Vibration Testing of Two Masonry Monuments in Cyprus - Tantele, Elia; Chrysostomou, Christis; Votsis, Renos; Kyriakides, Nicholas (My University, 2012)
The current study investigates the dynamic characteristics of two historical monuments in Cyprus, the St. Nicholas Cathedral in Famagusta and the St. Mamas Church in Morphou. The testing was performed using the ambient vibration survey approach and the output-only method for both structures, to obtain the frequencies and mode shapes of the lower modes. These results contributed in the updating of the finite element models and in the planning of the monitoring strategy that was implemented for these structures, as well as the study for their seismic vulnerability. Comparisons are made between the measured and finite element model dynamic characteristics, and conclusions are drawn.
Keywords: Soil mechanics--Abstracts; Geotechnical engineering; Famagusta (Cyprus)--History